(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
Demonstrating by a literary review, followed by field data collection in a rural company of Indaial, state of Santa Catarina (SC), the possible insertions of rural accounting in the management process of the small property is intended. All existing cultures in the property were analyzed, with the cucumber culture standing out as the one that offers the most financial return, which was the object of study of this work. In conclusion, after analyzing the year-end income statements, based on the months in which the property holds its best production cycle of all crops, the cucumber actually offers greater profitability for the producer. Since the production cycle of cucumber, cultivated outdoors, being in summer, due to its natural characteristics, in the colder months the income of the property reduces significantly. To this end, alternatives were sought, alongside the producer, to mitigate the income decrease in this period of production seasonality.